2020
DOI: 10.1177/1362168820912354
|View full text |Cite|
|
Sign up to set email alerts
|

Task repetition, synchronous written corrective feedback and the learning of Korean grammar: A classroom-based study

Abstract: Recently, there has been a shift in the perception of tasks. Tasks are no longer viewed as ‘one-off’ activities, and the importance of studying the role of task repetition has been increasingly addressed (Bygate, 2018). However, the way task repetition effects are mediated by other instructional conditions such as corrective feedback has not been widely researched. The current study examined the effects of task repetition and indirect synchronous written corrective feedback (WCF) during collaborative writing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…These results contribute to the mounting evidence from task repetition research that task familiarity contributes positively to positive experiences during task completion ( Author , xxxx; Kim, 2013 ; Pinter, 2015 ). To the best of our knowledge, Kim et al (2020) are the first to examine the influence of task repetition, but with teacher-provided synchronous feedback, and reported that students’ stress decreased after having performed the task on multiple occasions. Furthermore, the modality-specific finding corroborates those of Author (xxxx) who examined the impact of two task repetition conditions (identical task repetition and procedural task repetition) on flow.…”
Section: Discussionmentioning
confidence: 99%
“…These results contribute to the mounting evidence from task repetition research that task familiarity contributes positively to positive experiences during task completion ( Author , xxxx; Kim, 2013 ; Pinter, 2015 ). To the best of our knowledge, Kim et al (2020) are the first to examine the influence of task repetition, but with teacher-provided synchronous feedback, and reported that students’ stress decreased after having performed the task on multiple occasions. Furthermore, the modality-specific finding corroborates those of Author (xxxx) who examined the impact of two task repetition conditions (identical task repetition and procedural task repetition) on flow.…”
Section: Discussionmentioning
confidence: 99%
“…Young learners were examined in Cánovas , Lázaro-Ibarrola (2021) and Roothooft et al (2022). Chandler (2003), Ekanayaka and Ellis (2020) and Kim et al (2022) studied university students, while Martínez-Esteban and Roca de Larios (2010) investigated secondary-school students, and Sánchez (2019) examined both university and secondary-school students. Individual and collaborative writing were studied in Lázaro-Ibarrola (2021) as well as Martínez-Esteban and Roca de Larios (2010), while collaborative writing alone was analyzed in Cánovas and Kim et al (2022).…”
Section: The Relationship Between Wcf and Writing Fluency: Empirical ...mentioning
confidence: 99%
“…The remaining studies focused on individual writing. Chandler's (2003) first reported study resorted to indirect WCF, Ekanayaka and Ellis (2020) used direct, semi-focused WCF, synchronous indirect WCF was selected by Kim et al (2022), while Chandler's (2003) second study and Sánchez (2019) drew upon both direct and indirect WCF. Cánovas , Lázaro-Ibarrola ( 2021) and Martínez-Esteban and Roca de Larios (2010) used models, which were also employed by Roothooft et al (2022) together with direct WCF.…”
Section: The Relationship Between Wcf and Writing Fluency: Empirical ...mentioning
confidence: 99%
See 2 more Smart Citations